Teknik Intervensi Meningkatkan Efikasi Diri sebagai Upaya Promotif Aktivitas Fisik pada Remaja - Saras Anindya Nurhafid; Astuti Yuni Nursasi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Self-efficacy has proven to be an important determinant of adolescent physical activity behavior. However, there are still knowledge gaps related to how intervention techniques can improve the self-efficacy of physical activity behavior in adolescents. This systematic review aims to describe the techniques of intervening adolescent physical activity aimed at increasing self-efficacy. Data collection uses several electronic databases namely ScienceDirect, Elsevier, Proquest, Jstor, Wiley Online Library by using the help of remote Lib UI and Google Scholar. Keywords used in literature search are related to self-efficacy, physical activity, adolescent, innovation and promotion of physical activity. The results show that the most widely used technique is to build mastery experiences by asking participants to engage in physical activity during the intervention and outside the intervention session, providing physiological feedback, setting goals, monitoring themselves and seeing the intervention giver and others practicing the intervention. The results of the study are expected to be a reference for researchers and developers of interventions in increasing the self-efficacy of adolescent physical activity behavior so that it has positive implications for the development of youthful physical activity promotion efforts. Further research is expected to be able to analyze the most effective intervention techniques to improve the selfefficacy of adolescent physical activity behavior Keywords: physical activity; teenager; intervention techniques; self efficacy ABSTRAK Efikasi diri telah terbukti menjadi penentu penting perilaku aktivitas fisik remaja. Namun, masih ada kesenjangan pengetahuan terkait tentang bagaimana teknik intervensi yang dapat meningkatkan efikasi diri perilaku aktivitas fisik pada remaja. Tinjauan sistematis ini bertujuan untuk menggambarkan teknik intervensi aktivitas fisik remaja yang bertujuan meningkatkan efikasi diri. Pengumpulan data menggunakan beberapa database elektronik yaitu ScienceDirect, Elsevier, Proquest, Jstor, Wiley Online Library dengan menggunakan bantuan remote Lib UI dan google scholar. Kata kunci yang digunakan dalam pencarian literatur berkaitan dengan self efficacy, physical activity, adolescent, innovation dan promotion physical activity. Hasil menunjukkan bahwa teknik yang paling banyak digunakan adalah membangun pengalaman penguasaan dengan meminta peserta melakukan aktivitas fisik pada saat intervensi dan di luar sesi intervensi, pemberian umpan balik fisiologis, penetapan tujuan, pemantauan diri serta melihat pemberi intervensi dan orang lain mempraktikkan intervensi. Hasil penelitian diharapkan bisa menjadi referensi bagi para peneliti dan pengembang intervensi dalam meningkatkan efikasi diri perilaku aktivitas fisik remaja sehingga memiliki implikasi positif bagi pengembangan upaya promotif aktivitas fisik remaja. Penelitian lebih lanjut diharapkan mampu menganalisis teknik intervensi yang paling efektif untuk meningkatkan efikasi diri perilaku aktivitas fisik remaja Kata kunci: aktivitas fisik; remaja; teknik intervensi; efikasi diri